2017
DOI: 10.1093/sleep/zsx091
|View full text |Cite
|
Sign up to set email alerts
|

What sways people’s judgement of sleep quality? A quantitative choice-making study with good and poor sleepers

Abstract: Study objectives:We conceptualized sleep quality judgment as a decision-making process and examined the relative importance of 17 parameters of sleep quality using a choice-based conjoint analysis.Methods:One hundred participants (50 good sleepers; 50 poor sleepers) were asked to choose between 2 written scenarios to answer 1 of 2 questions: “Which describes a better (or worse) night of sleep?”. Each scenario described a self-reported experience of sleep, stringing together 17 possible determinants of sleep qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 67 publications
(73 reference statements)
0
30
0
10
Order By: Relevance
“…This resonates with sociological research which suggests that men engage with sleep via a function/non-function balancing act and believe that you should get just enough sleep to be able to function (especially in paid employment), but not so much that it reduces the time you have awake to perform work roles and other valued activities (Meadows et al, 2008; see also Coveney, 2014). Recent clinical studies have also suggested that sleep quality judgements are influenced by activities upon waking and the day after (Ramlee et al, 2017).…”
Section: Sleep Is Liminalmentioning
confidence: 60%
“…This resonates with sociological research which suggests that men engage with sleep via a function/non-function balancing act and believe that you should get just enough sleep to be able to function (especially in paid employment), but not so much that it reduces the time you have awake to perform work roles and other valued activities (Meadows et al, 2008; see also Coveney, 2014). Recent clinical studies have also suggested that sleep quality judgements are influenced by activities upon waking and the day after (Ramlee et al, 2017).…”
Section: Sleep Is Liminalmentioning
confidence: 60%
“…The quality of sleep is predetermined for respondents and may have been associated with symptoms of sleep disorders. Sleep breathing disorder is a condition for several chronic conditions in which partial or complete disruption of breath occurs many times throughout the night, resulting in daytime sleepiness or fatigue, limiting the functional ability of the individual and reduces his quality of life [8]. Moreover, the fear of death as well as the negative progression of the disease are of great concern to patients who develop sleep apnea [9] with predominant disorder, insomnia [1].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies emphasize the need to have healthy rest and sleep in order to be able to perform our regular activities, 24,25 but this is not our case, since most people experience sleeping difficulty as an issue that is consistent with the results of other research studies 26 ; sleep-associated disorders seem to be one of the most relevant problems and are considered part of cognitive disorders with significant impact on memory and affective behavior. Furthermore, in our studies, participants claim that pain worsens during the night time, making it difficult to fall asleep (which is similar in other studies), 27,28 when studying the characteristics of the disease in different population groups.…”
Section: Discussionmentioning
confidence: 81%